Estimation of the joint survival function for three successive duration times under double truncation and right censoring - Shen, Pao-sheng (Journal of statistical computation and simulation, 2019)
In incident cohort studies, it is common to include subjects who have experienced a certain event within a calendar time window. For all the included individuals, the time of the previous events is retrospectively confirmed and the occurrence of subsequent events is observed during the follow-up periods. During the follow-up periods, subjects may undergo three successive events. Since the second/third duration process becomes observable only if the first/second event has occurred, the data is subject to double truncation and right censoring. We consider two cases: the case when the first event time is subject to double truncation and the case when the second event time is subject to double truncation. Using the inverse-probability-weighted approach, we propose nonparametric and semiparametric estimators for the estimation of the joint survival function of three successive duration times. We establish the asymptotic properties of the proposed estimators and conduct a simulation study to investigate the finite sample properties of the proposed estimators.